Characteristics of natural killer cells in Malaysian HIV patients presenting with immune restoration disease after ART - Tan, D.; Yong, Y.; Tan, H.; French, M.; Kamarulzaman, A.; Price, Patricia (2010)
Objectives: Natural killer (NK) cell function was investigated in Malaysian HIV patients beginning antiretroviral therapy (ART) with advanced immunodefi ciency. Some patients experienced immune restoration disease (IRD) presenting as exacerbations of pre-existing infections. Whilst most IRD are attributed to interferon-gamma (IFN?) produced by T-cells, NK cells may also contribute. Methods: Blood leukocytes were collected prospectively from 100 HIV patients over 1 year on ART, plus 36 healthy controls. Eleven patients who experienced an IRD and 14 matched controls were assayed. Cells producing IFN? were quantitated by ELISpot after stimulation with an NK target (K562 cells) or antigens from pathogens associated with the IRD. NK cell subsets, CD16 and perforin expression were determined by fl ow cytometry. Results: NK cell IFN? responses were lower in HIV patients at baseline (p<0.001), improved by Week 24 (p<0.01) but remained lower than uninfected controls (p<0.05). Proportions of CD56hi NK cells increased (p<0.01) above controls at Week 24. Perforin expression on these cells was higher than controls at baseline (p<0.01), but declined on ART. Proportions of CD56 lo NK cells were similar in patients and controls throughout. IRD patients showed lower CD16 expression on CD56lo NK cells than non-IRD patients before treatment (p<0.05). Conclusions: NK cells profi les were restored on ART, but NK cell IFN? production remained impaired. Low CD16 expression on CD56lo NK cells may mark a predisposition for an IRD. © 2010 Tan DBA, et al.